REAKTUALISASI KURIKULUM PENDIDIKAN AGAMA ISLAM INTEGRATIF (TELAAH KRITIS KOMPARATIF DI PESANTREN, SEKOLAH, DAN MADRASAH) - Sufirmansyah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
As a globalization’s response, integrative Islamic Education curriculum reactualization is a must to fix it’s quality and existence. Therefore, this article will examine integrative Islamic Education curriculum reactualization in pesantren, school, and madrasah. Former reference literatures will be more explored to get the synthesis of integrative Islamic Education curriculum in pesantren, school, and madrasah. In pesantren organization, integrative Islamic Education curriculum reactualization practiced by applying many subject and various learning method. Integrative Islamic Education curriculum reactualization in school including utilizing various learning method and strategy. Islamic Education in public school carried out as an effort to integrating Islamic Education into school system with common knowledge oriented curriculum. It require good cooperation between teacher to synergyzed Islamic Education subject with common knowledge subject.